2008
DOI: 10.1016/j.neuroimage.2007.08.029
|View full text |Cite
|
Sign up to set email alerts
|

Statistical mapping of sound-evoked activity in the mouse auditory midbrain using Mn-enhanced MRI

Abstract: Manganese-enhanced MRI (MEMRI) has been developed to image brain activity in small animals, including normal and genetically modified mice. Here, we report the use of a MEMRI-based statistical parametric mapping method to analyze sound-evoked activity in the mouse auditory midbrain, the inferior colliculus (IC). Acoustic stimuli with defined frequency and amplitude components were shown to activate and enhance neuronal ensembles in the IC. These IC activity patterns were analyzed quantitatively using voxel-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 37 publications
2
68
0
Order By: Relevance
“…Therefore, to track brain activity in awake, freely moving animals, we used a modified MEMRI protocol that decouples isofluorane anesthesia and DOI administration. Previously, MEMRI was successfully applied to analyze cocaine-, sound-, and odor-induced activities (9,11,12,21), as well as brain plasticity in song birds (10). Because Mn 2+ can be neurotoxic (22,23), we carried out a pilot experiment on naive, 6-wk-old C57BL/6J mice to establish a protocol and study the effects of Mn 2+ on general animal health and DOI-induced behavior.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, to track brain activity in awake, freely moving animals, we used a modified MEMRI protocol that decouples isofluorane anesthesia and DOI administration. Previously, MEMRI was successfully applied to analyze cocaine-, sound-, and odor-induced activities (9,11,12,21), as well as brain plasticity in song birds (10). Because Mn 2+ can be neurotoxic (22,23), we carried out a pilot experiment on naive, 6-wk-old C57BL/6J mice to establish a protocol and study the effects of Mn 2+ on general animal health and DOI-induced behavior.…”
Section: Resultsmentioning
confidence: 99%
“…By taking advantage of the fact that Mn 2+ enters excitable cells via voltage-gated calcium channels, MEMRI has been used to study cocaine-induced neuronal activity (9), brain plasticity in song birds (10), and sound-evoked activity (11,12). The approach in the first two studies has some limitations, as it is invasive, whereas the latter study required exposure to a prolonged, repetitive stimulus.…”
Section: Oss-mentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that microtubules contribute to, although probably are not fully responsible for, the axonal transport of 54 Mn (Sloot and Gramsbergen, 1994) and the same mechanism would be expected for 52 Mn. Furthermore, studies utilizing non-radioactive Mn 2+ have shown that the transport, as well as the uptake, depend on neuronal activity, and that voltage-gated Ca and Na channels are involved in these processes (Lin and Koretsky, 1997, Yu et al, 2008, Wang et al, 2015.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This technique was shown to identify activated regions of the rodent brain which "light-up" in T 1 -weighted images following auditory [117,118] or somatosensory stimulation [3,50,113], performed after injection manganese chloride [50]. However, the fact that this technique requires general anesthesia and opening of the blood brain barrier, as well as the toxicity of manganese, are issues that need to be considered [30] in order to fully exploit the potential of MEMRI for imaging plasticity, testing behavioral paradigms, or studying the effects of pharmacological agents or substances of abuse on the central nervous system [73].…”
Section: Brainmentioning
confidence: 99%